The impact of Central Asian tourists’ risk perception on their travel intentions during the COVID-19 pandemic - Saidmamatov, Olimjon; Khodjaniyazov, Elbek; Matyakubov, Umidjon; Ibadullaev, Ergash; Bekjanov, Dilmurad; Day, Jonathon; Marty, Peter; Zhao, Jinlin (Turyzm/Tourism, 2021)
Central Asian (CA) countries (Kazakhstan, Kyrgyzstan, Turkmenistan, Tajikistan, Uzbekistan) are assumed to be one of the most attractive tourist destinations since this particular geographical location holds immense potential in tourism products. Due to the COVID-19 pandemic, the flourishing tourism sector of these countries has been immensely affected. The aim of this study is to examine the impact of Central Asian tourists' risk attitudes toward traveling during the COVID-19 pandemic through consideration of sociodemographic characteristics. The research was conducted during January through April 2021 based on a sample of 966 respondents via an online questionnaire. In the survey, risks are divided into four main categories: health, psychological, financial and travel destination. Nominal regression was used to identify the way in which risk perception affected travel intentions during COVID-19 and the research findings indicate that Central Asian tourists’ risk perception has done so. Hygiene, disinfection and a reliable health system in destinations (21%) will be leading factors in future travel.